(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
Camila Tiago is an lighting director of the Theater course at the Federal University of Uberlândia – UFU, where she also founded a group of studies in stage lighting called “Cênica Luz”. Born in Iturama and raised in Uberlândia, both in Brazil, she is one of the coordinators and hosts of the weekly program “from idea to light” and works professionally as a lighting designer for some of the most important theater groups in her region, such as Grupo Pontapé. Kindly, she talks about professional qualification, research, creation and other peculiarities that involve the lighting profession in Brazil, more specifically in her region. With a trajectory built on the foundations of self-taught, Camila has been establishing a constant relationship with research and, mainly, with practice, as she tells us throughout this generous interview.